“Esophageal surface cell in Non-Erosive Reflux Disease” : Scanning Electron Microscopic study (SEM)” - Myint, Yi Yi; Tun, Ye; Mohammad Amjad, Nasser; Abdul Rashid, Nor Linda; Mat Hassan, Mohd. Zailani (2011)
Background: Non-erosive reflux disease (NERD) is the most common phenotype of gastro esophageal reflux disease. Dilated intercellular spaces (DIS) in prickle cell layers are considered as early signs of acid damage to the esophageal epithelium. In order to enter the mucosal intercellular spaces, acid and pepsin have to penetrate the intercellular adhesion sites of the most superficial epithelial cells. Objectives: The aim of this study is to explore cellular attachments in most superficial esophageal cells of NERD patients and to find out any association between reflux symptoms and DIS. Material and methods: The study group included 8 NERD patients with reflux symptoms, normal mucosa on endoscopy and positive 24-hour pH monitoring (NERD) and 5 normal controls. Specimens were routinely processed for SEM. The nature of cellular attachment and intercellular spaces between superficial cells of esophageal mucosa were viewed by SEM. Statistical analysis: The association between DIS and categorical data as well as reflux symptoms was accessed by using Chi-Square test & Fisher’s exact test respectively. p <0.05 were considered to be statistically significant. Results: We found out that cellular attachments in the superficial cells differ significantly among the normal controls and patients with NERD (p value 0.007) .There was no association between both heartburn and acid regurgitation with DIS as the p value were 0.128 and 0.487 respectively. Discussion: Our results showed that DIS was found in all NERD patients and 3 out of 5 (60%) controls. This is because SEM only views the surface cells of the epithelium and even in normal, the surface cells are terminally differentiated and in varying stages of being desquamated into the lumen. Conclusions: We can conclude that SEM study on DIS in esophageal surface cells is not a useful diagnostic test for differentiating between normal and NERD patients.